Association between salivary alpha-amylase and subjective and objective oral parafunctions in community-dwelling elderly individuals - Koji Morita; Hitomi Kimura; Hiroki Tsuka; Fumiko Nishio; Mitsuyoshi Yoshida; Kazuhiro Tsuga (Elsevier, 2020)
Background/purpose: Stress in the elderly is caused by loss of physical and psychological health. Although there have been many reports on the intraoral environment affecting physical health, few reports exist on stress and the intraoral environment in the elderly. The aim of this study was to investigate the relationship between salivary α-amylase as an index of stress value and the intraoral environment. Materials and methods: Three hundred and nineteen participants were community-dwelling independent individuals over 65 years old. The outcome variable was salivary α-amylase. After measurement, salivary α-amylase was classified into four groups (0 = 0-30, 1 = 31-45, 2 = 46-60, 3 = 61-200). The predictor variables were physical status (which includes age and male body-mass index) and subjective and objective symptoms (which include present teeth, torus palatinus, torus mandibularis, temporomandibular joint noise, bruxism, and dental attrition). These variables were compared among participants using univariate analysis and multiple logistic regression analysis. Results: The participants included 77 men and 242 women, with a mean age of 75.8 ± 5.4 years (65-94 years). Although temporomandibular joint noise and dental attrition were significantly positively correlated with salivary α-amylase, bruxism was significantly negatively correlated with salivary α-amylase (p < 0.05). Stepwise regression analysis revealed a significant relationship between salivary α-amylase and temporomandibular joint noise, bruxism, and dental attrition. Conclusion: High salivary α-amylase is associated with a high rate of temporomandibular joint noise and dental attrition, and a low rate of bruxism among elderly participants.